The Use of Nanoparticles in Targeted Drug Delivery and Imaging in Oncology - Khadir, Ali Abdul Hussein Musafir; Odeh, Mohammed Jaafar Hamid; Muslim, Zainab Mohammed Ali; Hilan, Abdullah Abdul Wahid; habl, Hussein jabbar Hamdullah (American Journal of Botany and Bioengineering, 2024)
Oncology has been seeing a fairly dramatic shift towards targeted drug delivery, and the use of nanoparticles is the trend out in front. Many different types of nanoparticles are being investigated and used to deliver drugs directly to cancer cells and act as imaging agents to help care professionals diagnose and manage the course of the disease. Since some of the most promising methods today are also areas of study, there is a great deal of discovery each year in the way that nanoparticles can target cells, carry imaging agents, and treat small cancers in need of treatment. The central aim of the current study discusses the importance of the development of nanoparticles in targeted drug delivery and the enhanced efficacy of imaging systems, particularly in oncology. Obviously, this way of research application has a promising future in improving the lives of oncological patients. The second objective is to overview the outcomes of modern studies devoted to the application of nanoparticles as targeting drugs enhancing their effectiveness. Shadowing of passive targeting performed using the EPR effect will not be displayed since its effectiveness is not doubted nowadays. Likewise, there is a plethora of source information on how long nanocarriers will keep providing accumulation in tumors. The means of treatment and diagnosis are steadily enhanced according to the recent advances in technological development in the bioscience fields, nanoengineering, and nanomaterials. Especially in oncology, where the increased mortality and morbidity rates continue to be a considerable problem all over the world, effective treatments and credible diagnostic methods are highly in demand. In fact, cancer is referred to as an evading disease at earlier stages, who also reinforce starting treatment at advanced stages with terrible disease outcomes, and they emphasize the urgent requirement for advancements to use a different approach in cancer care practices. Such advances are termed ’highly promising’, which gains prominence in precision oncology approaches. This document could attract the reader and inspire them to read the whole document.